2019
DOI: 10.30699/ijmm.13.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dominant Serovars and Molecular Analysis of hly and iap Genes Related to Listeria monocytogenes Strains Isolated from Spontaneous Human Abortions in Tehran

Abstract: Article Subject: Molecular Microbiology DOI: Background and Aims: Listeria monocytogenes, a gram positive, facultative, intracellular bacterium is the causative agent of listeriosis that is transmitted to human through raw and ready-to-eat foods. The aim of the present study was to determine dominant serovars of L. monocytogenes isolated from spontaneous abortion using phenotypic and genotypic methods. Materials and Methods: In present study, 258 clinical specimens including placental secretions, vaginal swabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Act A in L. monocytogenes encodes the surface protein act A, which is responsible for actin-based motility and cell-to-cell spread ( Vàzquez-Boland et al, 2001 ). Rezaei et al (2019) showed that the presence of hly A and iap in L. monocytogenes is effective in increasing its aggressiveness and pathogenicity. Cellular invasion requires the presence of bacterial surface proteins internalin A ( inl A) and/or inl B and their interaction with the cellular receptors E-cadherin and/or Met, respectively ( Kühbacher et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Act A in L. monocytogenes encodes the surface protein act A, which is responsible for actin-based motility and cell-to-cell spread ( Vàzquez-Boland et al, 2001 ). Rezaei et al (2019) showed that the presence of hly A and iap in L. monocytogenes is effective in increasing its aggressiveness and pathogenicity. Cellular invasion requires the presence of bacterial surface proteins internalin A ( inl A) and/or inl B and their interaction with the cellular receptors E-cadherin and/or Met, respectively ( Kühbacher et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Listeriamonocytogenes, an intracellular and opportunistic pathogen, enter the body through contaminated water and food and cause a systemic infection called listeriosis, which in turn causes meningoencephalitis in pregnant women, the elderly, and those with immunodeficiency (13). The clinical spectrum of listeriosis contains two specific targets; the placental-maternal unit and the central nervous system (15). Listeriosis in pregnant women is asymptomatic or has mild flu-like symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These problems can affect especially those patients with a background disease or severe conditions, and other high-risk individuals such as pregnant women, and unborn or newborn babies and immunocompromised persons. The incidence of listeriosis among pregnant females with a history of spontaneous abortion is 12 per 100,000, while its prevalence is reported as 0.7 per 100,000 in healthy individuals, and about one-third of reported human listeriosis cases are associated with recurrent abortion (15). L. monocytogenes can cause inflammation in the placenta or amniotic sac, fetal infection, and even abortion or stillbirth as the bacteria can cross the placenta barrier (16).…”
Section: Introductionmentioning
confidence: 99%
“…2018). ActA in L. monocytogenes encodes the surface protein actA, which is responsible for actin-based motility and cellto-cell spread (Vàzquez-Boland et al 2001) Rezaei et al (2019). showed that the presence of hlyA and iap in L. monocytogenes is effective in increasing its aggressiveness and pathogenicity.…”
mentioning
confidence: 99%